Le sport sous l`occupation : regards croisés sur les chiffres rendus par le Commissariat général à l`éducation générale et aux sports (1940-1942) - Terfous, F. (Science et motricité, 2011)
Sport under occupation is most often linked, in literature, politics of the Commissioner general to the general education and sports (CGEGS). This paper aims to modify sports scores developed by CGEGS proposing to quantify and qualify the sports associations reported and published in official newspapers between 1940 and 1942. Our analysis is based on the one hand, on a review of statistical studies on the sport of CGEGS, and, secondly, on an archival practice. In fact, statistics CGEGS are biased, partial and fragmented.